Peran Badan Penanggulangan Bencana Daerah Kabupaten Langkat dalam Mengedukasi Masyarakat Daerah Aliran Sungai di Desa Stabat Lama Barat Kecamatan Wampu Kabupaten Langkat - Taufik Ramadhan; Randa Putra Kasea Sinaga (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Disaster management is a process that involves understanding, planning and implementing measures designed to reduce the impact of disasters on communities and the environment and to reduce disaster risk. In terms of disaster management efforts, institutions have a huge role in society. The Regional Disaster Management Agency (BPBD) is a government agency whose scope of duties focuses on disaster management in the community to the regions. One area that is often hit by disasters is the watershed. Communities living around watersheds often face problems such as erosion of the land surface they live on, landslides, overcrowded settlements, sanitation, and flooding. Faced with this, BPBD participates in educating the community which is very necessary so that the community understands the problems and potential disasters that exist in their area. This study aims to determine how the role of BPBD Langkat district in educating the community in the Sei Wampu watershed area, Stabat Lama Barat village, Langkat district. The data collection technique used was observation and interviews. Based on the research that has been done, the results of this study indicate that the BPBD of Langkat Regency through the program to educate the community has succeeded in carrying out its role as a regulatory organizer, provider of services, and as a community organizer.